British-Bangladeshi immigrants and the local political landscape in Bangladesh - Haque, Kazi Nurmohammad Hossainul; Biswas, Sanjay Krishno (Taylor and Francis Inc., 2016)
This book chapter was published in International Migration and Development in South Asia [© 2015 Taylor and Francis Inc.] The book chapter's definite version is available at: :http://dx.doi.org/10.4324/9781315709088.